Dealing with Communicative Problems in English as a Lingua Franca - Nowicka, Agnieszka (Kalbotyra, 2008)
The aim of the article is to discuss, first, how the differences in socio-cultural interaction styles can influence communication, second, what is interaction participants’ orientation to the problems originating in those differing styles and finally, how such troubles are negotiated, and more specifically, repaired in communication. Conversation analysis (CA) will be used to analyze an illustrative excerpt of interaction in English. [...]